2022
DOI: 10.3389/fpubh.2021.833970
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Prediction Model for Cancer-Specific Survival of Elderly Patients With Clear Cell Renal Cell Carcinoma: A Population-Based Study

Abstract: BackgroundClear cell renal cell carcinoma (ccRCC) is expected in the elderly and poor prognosis. We aim to explore prognostic factors of ccRCC in the elderly and construct a nomogram to predict cancer-specific survival (CSS) in elderly patients with ccRCC.MethodsClinicopathological information for all elderly patients with ccRCC from 2004 to 2018 was downloaded from the Surveillance, Epidemiology, and End Results (SEER) program. All patients were randomly assigned to a training cohort (70%) or a validation coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Previous virus studies have developed nomograms for predicting the OS and CSS of multiple databases. Moreover, it has shown promising clinical potential value in renal cancer, endometrial stromal sarcoma, glioma, nephroblastoma, and other cancers (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Previous virus studies have developed nomograms for predicting the OS and CSS of multiple databases. Moreover, it has shown promising clinical potential value in renal cancer, endometrial stromal sarcoma, glioma, nephroblastoma, and other cancers (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the chance of genetic mutations causing cancer increases with age. Studies have shown that age plays a key role in the survival of various cancers ( 15 , 16 ). A prediction study on non-spermatogonial cell tumors found that the survival rate of adolescent patients was higher than that of adults ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…A nomogram is a popular prognostic tool with the ability to predict clinical events by integrating potential risk factors (3). Nomograms have been widely used for tumor prognosis (4)(5)(6) and have been effectively used to predict short-term and long-term survival for asymptomatic adults undergoing screening for cardiac risk factors (7). Thus, we hypothesized that a nomogram may also be feasible for the risk stratification of critically ill patients undergoing ECMO.…”
Section: Open Access Edited Bymentioning
confidence: 99%